The Role Of Folk Games In Raising Children’s Thinking And Forming A Culture Of Recreation - Marguba Adilovna Akbarova (The American Journal of Social Science and Education Innovations, 2021)
The article analyzes the role of folk games in the development of children’s thinking and the formation of a culture of recreation with the help of data from the scientific literature. In addition, games have been studied to help children understand and influence the world around them, to develop their mental, moral, volitional and physical qualities, and to educate people through play.